Pengaruh Brand Image dan Brand Love Terhadap Customer Loyalty dengan Customer Engagement sebagai Mediasi (Studi pada Konsumen Produk Wardah Kosmetik di Kota Malang) - Rizqi Nurfitriana ; Prof. Dr. Surachman, SE., MSIE.,Ananda Sabil Hussein, SE., M.Com., Ph.D
This study aims to discover the influence of brand image, brand love, and customer engagement on customer loyalty of costomers of Wardah Cosmetics in Malang. This study is an explanatory study with quantitative approach and Partial Least Squares (PLS) was selected as the survey method along with nonprobability sampling with purposive sampling technique to collect the data on the 150 respondents in Malang. The results of this study show that the brand image and brand love simultaneously have significant effect on customer engagement. While the brand love has a significant effect on customer loyalty and on the other side, the brand image has no significant effect on customer loyalty. Furthermore, the customer engagement is also found to act as a mediator in this study and also is proven to give positive and significant effect on customer loyalty. In conclusion, the results of this study is able to help the practitioners to enhance the customer loyalty on their company based on brand image, brand love and customer engagement. The result of this study is expected to be a reference for future research. _x000D_ _x000D_ _x000D_ _x000D_ Keywords: Brand Image, Brand Love, Customer Engagement, Customer Loyalty